Representations of Palestinians in Hollywood feature movies from 2000 to 2014 - Adeeb, Jnaidi Saed Maher (2019)
Since the period followed the September 11 in 2001 attack, and the second Palestinian uprising in 2000, Hollywood has produced many feature movies representing the Arab, whether related totally to the Palestinian-Israeli conflict or partially related to the Palestinian character. The representation was shown in certain positions and scenes in the feature movie to give a certain meaning. Further, most of these studies have examined the personality and the Palestinian cause in Hollywood feature movies combined with Arab characters. However, this study seeks to examine the Palestinian character represented in Hollywood feature movies from 2000 to 2014 in detailed analysis. A literature analysis reviewed the Arab and Palestinian representations in Hollywood feature movies. Moreover framing theory has been used as a guide. The quantitative approach is adopted as well as the data has been collected by employing the quantitative content analysis through using a coding sheet. The sample selection of this study is total population sampling of 5 Hollywood feature movies with total duration 655min. The unit analysis is 71 scenes which include and involve Palestinian character(s) within the five Hollywood feature movies. This study has approved that after the period that followed the second Palestinian uprising in 2000 and September 2001 attack, the Palestinian depiction began to change. Thus, The Palestinian character has represented in more complexity than the previous representation. Additionally, this study has observed that, after the attack, Hollywood has modified the Palestinian representation. There is no agreement on one frame of the Palestinian representation among the filmmakers. Hence, the study confirmed that there is a measure of positive representation of the Palestinian character, yet with the major-negative stereotype.